Effect of change point and imperfect debugging in software reliability and its optimal release policy - Chatterjee, Subhashis; Nigam, Shobhit; Singh, Jeetendra Bahadur; Upadhyaya, Lakshmi Narayan (Mathematical and computer modelling of dynamical systems, 2012)
This article presents a software reliability growth model based on non-homogeneous Poisson process. The main focus of this article is to deliver a method for software reliability modelling incorporating the concept of time-dependent fault introduction and fault removal rate with change point. Also in this article, a cost model with change point has been developed. Based on the cost model optimal release policy with change point has been discussed. Maximum likelihood technique has been applied to estimate the parameters of the model. The proposed model has been validated using some real software failure data. Comparison has been made with models incorporating change point and without change point. The application of the proposed cost model has been shown using some numerical examples.